Protein-polysaccharide microcapsules formed on matrices of different structures - Viktoria Evgen'evna Suprunchuk; Evgenija Vladimirovna Denisova (Наука. Инновации. Технологии)
In this paper we consider the possibility of forming microcapsules by layer-by-layer adsorption of polymers on inorganic cores and polymeric nature. Removal of the carbonate cores were performed by lowering the pH of the system to 4.5. Removal of the polypropylene matrix were carried out using tetrahydrofuran in the case of polystyrene media. It is established that the nature of the matrix used for the formation of microcapsules, affect the degree of incorporation of protein and the yield of polyelectrolyte particles.